If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(T)=2T-4
We move all terms to the left:
(T)-(2T-4)=0
We get rid of parentheses
T-2T+4=0
We add all the numbers together, and all the variables
-1T+4=0
We move all terms containing T to the left, all other terms to the right
-T=-4
T=-4/-1
T=+4
| -5x+3=4x+12 | | 2+3+3x15= | | 2x+11+4x+1=90 | | 15n+5=10 | | m3=100,m2 | | 77+3x+1=180 | | -8-(x-4)=6x+5(4-x) | | 77+3x+1=90 | | 6x=2x+48= | | 2x+x+21=90 | | 3+4+(4x15)=x | | -243=(-9)(10+x) | | N=6x+9 | | m14=75,m2= | | 25=c×c | | 3b−13b=15+25 | | -4n+20=5n+2 | | F(x)=28-2.5x | | 5+2x+4x+1=90 | | 4n^2-17n-15=0 | | 80+3x-43=180 | | 2(y+2)4y=3(2y-)+8 | | (3x^2+4x-2)-(2x^2-3x-4)=0 | | -9-2x=x+15 | | -2x-7=-4x-3 | | P=9x-6 | | N=5x+10 | | 2(4+5x)+5(6x-4)=68 | | -3x+2=-14 | | 20x=30*24 | | 12-(a-1)=11+a | | |3x–7|+4=12 |